Edol Dance at Galungan Nadi Ceremony in Belancan Traditional Village, Kintamani District, Bangli Regency - Jaman, Ni Ketut; Nerawati, Ni Gusti Ayu Agung (International Journal of Multidisciplinary Sciences, 2023)
The development of science and technology influences people's mindset in various aspects of life including aspects of religious life as well as in understanding their religious teachings, both tattwa, morals and ceremonies. Temple is one of the symbols or symbols of the universe created by Ida Sang Hyang Widhi Wasa, Hindus view it as Stana Ida Sang Hyang Widhi Wasa and all of His manifestations. Bale Agung Temple in the Belancan Traditional Village is a Tri Kahyangan temple which has a special uniqueness that lies in the Piodalan ceremony which coincides with Galungan Nadi Day where the Edol dance tradition is being carried out. Edol Dance is a Sacred Dance in Belancan Village, Kintamani District, Bangli Regency. Edol dance is a sacred dance that is unique, one of which lies in its dance moves. The Edol dance has one movement that is performed repeatedly which is danced by young men or unmarried men. The movement in this dance has aesthetics because it includes three requirements, namely unity, balance and clarity. Unity can be seen from the movements in the dance supported by the dress, make-up, staging venue and dance accompaniment music according to the character of the dance and balance can be seen from the repetition of movements from front to back and from back to front due to the structure in the dance. This study aims to determine the performance of the Edol Dance at the Galungan Nadi ceremony in the Belancan Traditional Village, Kintamani District, Bangli Regency and to find out the ceremonial facilities needed for the Edol Dance performance and to find out the extent of the participation of the Edol Dance in the Galungan Nadi ceremony. The method used in this study is a qualitative method in which informants are determined using the sampling subject method, and the data collection method used is the method of interviewing and recording documents while processing the data using descriptive analysis methods. The result and discussion is the history of Belancan Village which started from the journey of I Gusti Wayahan who hid in the wilderness. The form of carrying out the Edol Dance tradition is Piodalan at Bale Agung Temple in Belancan Village which falls every Galungan Nadi Day. The facilities needed before the performance of the Edol Dance are a set of offerings of segehan agung complete with a black chicken to be slaughtered, bayuan, petas, 4 selnggi oujung rice supplemented with pork, a santun containing 775 kepeng coins. The Belancan Traditional Village plays a very important role, because apart from being a complement to the ceremony which is held every five years, namely the Galungan Nadi ceremony, especially at the end of the ceremony (nyineb) before the performance, the dancers are decorated with young palm leaves and all the village's male villagers. Men bring Prani offerings to Bale Agung Temple with the intention that the dancers are free from interference from other people or outside disturbances.